Drying Effect on Moisture Reduction and Tensile Strength Property of Polycarbonate - สิมประดิษฐ์พันธุ์, อรรถพล; รามประกาย, พิชัย; โอเจริญ, ณรงค์ชัย (Frontiers in Engineering Innovation Research, 2010)
Polycarbonate is plastic that have ability to absorb moisture. The moisture is caused to decreasing in character and many properties such as bubble, silver streak and mechanical properties, the drying process of polycarbonate pellets is needed. This research aimed to study drying effect on moisture reduction of polycarbonate pellets and tensile strength property of polycarbonate product. The polycarbonate pellets, which was initial moisture content of about 0.186-0.193% wet basis were dried at 80, 100 and 120 degree celsius for 5 hrs. by hopper dryer and rotary dryer with the hot air velocity of 0.4 and 4 m/s, respectively. The results showed that polycarbonate pellets of drying with rotary dryer had less residual moisture content than polycarbonate pellets of drying with hopper dryer, and polycarbonate product molded from dried polycarbonate pellets had higher tensile strength than polycarbonate product molded from non-dried polycarbonate pellets.